Productive Biological Diversity for Sustainability of the Small Farm - Jiménez, Wilbert (2004)
It’s briefly revealed the ‘farming economy for self-consumption’ nature of Costarrican society up to the twentieth century; an economy respectful of biological diversity and stimulant of productive di-versity. The Green Revolution, with its mechaniza-tion and massive use of artificial goods, came to stimulate monoculture and technological depen-dence. Agroforestal and forestry-pastoral systems, polyculture and mixed orchards are efficient forms of production, ecologically sustainable, that in dif-ferent places of America, even in Costa Rica, far-mers have maintained in spite of the Green Revo-lution and that should now be promoted.